THE IMPACT OF THE PERFORMANCE OF TERMINAL INSPECTION SERVICE (TIS) OFFICERS ON TOWARDS SERVICE - Liestia Septi, Awaliya; Ratna Sari, Dewi; Suprapto, Yuyun (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
PT Angkasa Pura has a unit in charge of supervising the facilities at the airport, namely the Terminal Inspection Service (TIS) unit which is in charge of supervising and ensuring that airport facilities ca function properly. This study aims to determine the effect of the airport facility supervision system carried out by every airport officer nationally referring to the Minister of Transportation Regulation Number 30 of 2021 concerning Minimum Service Standards for Air Transport Passengers. This research uses quantitative descriptive research methods. The research technique uses observation and questionnaire mathods. The instrument used to test the hypothesis is regression analysis. As for the calculation of the analysis is the Likert scale technique, validity test, reliability test, and hypothesis analysis. The result showed that the relationship between the influence of the performance of Terminal Inspection Service (TIS) officers and excellent service was strong and real 84.5% so that if the performance of the Terminal Inspection Service (TIS) officers is improved, excellent service will also increase.